Joint criminal enterprise as a pathway to convicting individuals for genocide - Sliedregt, Elies van (Journal of international criminal justice, 2014)
This article discusses one of the most controversial yet important modes of liability in international criminal law: joint criminal enterprise (JCE). One such controversy is whether Third Category JCE can serve as a basis for genocide convictions. To answer this question one needs to uncover the nature and origins of JCE. It is submitted that convictions for genocide based upon the application of Third Category JCE are justifiable. This contention stems from the premise that JCE is a form of criminal participation to which principles of derivative liability apply. However, such an approach is only valid when JCE is stripped to its core and applied as a small-scale group crime, which requires proof of a direct link between co-perpetrators. Moreover, in the case of Third Category JCE, a participant should be convicted of participating in genocide, which would carry a lower sentence than committing genocide as a participant in a First or Second Category JCE